Future challenges in evaluating and managing sustainable development in the built environment - 4 0 16; (Patrizia L.), Brandon, P. S. (Peter S.); Lombardi, P. L.;Shen, Qiping; 5 (Chichester, West Sussex, United Kingdom : Wiley-Blackwell, 2017)
Future Challenges in Sustainable Development within the Built Environment stimulates and reinterprets the demands of Responsible and Sustainable Development in the Built Environment for future action and development. It examines the methods of evaluation, the use of technology, the creation of new models and the role of human factors for examining and developing the subject over the next twenty years.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Sustainable development; 20; 2